Professional Didactics Engineering - Patrick Mayen; Paul Olry; Pierre Pastré (Universidade Federal do Oeste da Bahia, 2020)
The french research of Professional Didactics has an evolving research field and accumulation of results from research, since its emergence in the 90s. With strong assumptions made by other branches of study, Professional Didactics constitutes a theoretical corpus that allowed the evolution of notion of Professional Didactic Engineering, understood as a design capable of allowing the conception and description of professional training itineraries and the understanding of the complex notion of professional competence. Thus, the work, when describing the elements of a Professional Didactic Engineering, provides a systematic bias for research.